GE_GERICHTE P/7966/2012 vom 19. September 2013 - GE Cour de justice (2013)
DISPOSITIONS PÉNALES DE LA LSTUP; FIXATION DE LA PEINE; SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE; CONFISCATION(DROIT PÉNAL) | LStup.19.1; LStup.19.2; CP.47; CP.43; CP.69